Pengaruh Model Pembelajaran Kooperatif Tipe Number Heads Together ( NHT) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Fikih Di Kelas VIII MTSN 10 Agam - Nina Adelya; Salmi Wati; Charles Charles; Afrinaldi Afrinaldi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research was motivated by the low learning outcomes of class VIII FIKIH MTsN 10 Agam. Researchers see the low UTS scores and the way student learn is still lacking during the FIKIH learning process. The hypothesis and this research is that the use of the Number Heads Together (NHT). On the learning outcomes of class VIII FIKIH MTsN 10 Agam. This research is a quantitative research using a quasi – experimental research design. The population in this study were all students of class VIII MTsN 10 Agam and the sample classes were class VIII 2 and class VIII 4. The instrument that the researcher used was the results of the FIKIH subject test in the form of multiple choice questions. As many as 20 questions with als material. The result of the reseach conducted by the researcher showed that the percentage of students completeness was hinger than the percentage of students completeness in the control class average score of 79,76 in the experimental class while in the control class there where 21 students who achieved KKM only 8 students with an average of 62,38 with a percentage of 86% experimental completeness and control class completeness 38% influence of the Number Heads Together (NHT) cooperative learning model on student learning outcomes in the FIKIH alms subject class VIII MTsN 10 Agam